Demographic Factors Influencing the Utilization of Focused Antenatal Care Services in Jama'a Local Government Area, Kaduna State, Nigeria - Yaki, Peter Francis; O., Nworuh B.; O., Udujih G.; M., Mato B. D. (Darul Yasin Al Sys, 2025)
Focused Antenatal Care (FANC) is a critical intervention designed to improve maternal and neonatal outcomes by ensuring timely and appropriate healthcare during pregnancy. Despite its benefits, utilization remains sub-optimal in many low-resource settings, including Nigeria This study assessed the influence of demographic factors on the utilization of FANC services among pregnant women attending public secondary hospitals in Jama’a Local Government Area (LGA), Kaduna State. A hospital-based cross-sectional descriptive study was conducted among 301 pregnant women using structured interviewer-administered questionnaires. The data collected included socio-demographic information and FANC attendance history. Descriptive statistics and Chi-square tests were employed for data analysis using SPSS version 23. A p-value of less than 0.05 was considered statistically significant. The study found that only 10.6% of respondents completed at least four antenatal visits as recommended by the World Health Organization. Significant demographic predictors of FANC utilization included age (p=0.003), parity (p=0.002), educational status (p=0.001), and ethnicity (p=0.027). Women aged 25–34 years, with 1–3 children, and with secondary or tertiary education were more likely to complete four or more ANC visits. FANC utilization in Jama’a LGA is low, and key demographic factors significantly influence its uptake. Interventions targeting less-educated, younger, and high-parity women are needed to improve ANC attendance and maternal health outcomes in the Jama’a LGA, and Kaduna State in general.